DESIGN AND DEVELOPMENT OF AN INTERNET OF THINGS (IOT)-BASED SYSTEM FOR DETECTING ALCOHOL LEVELS, CIGARETTE SMOKE, AND ROOM TEMPERATURE IN HOSPITALS: Abstract - Komang Diva Andi Wirawan; I Ketut Resika Arthana; Ketut Agus Seputra (Jurnal Pendidikan Teknologi dan Kejuruan, 2026)
Air quality in hospitals is an important factor in ensuring the safety and comfort of patients and medical personnel. The presence of alcohol levels and cigarette smoke in hospitals can have a negative impact on health, occupational safety, and air quality, especially since alcohols such as ethanol and isopropanol are widely used as disinfectants and antiseptics. Exposure to high concentrations of alcohol levels can potentially cause respiratory tract irritation, nervous system disorders, and increase the risk of fire, while cigarette smoke contains carcinogenic substances that are harmful to both active and passive smokers. In addition, room temperature and humidity that do not meet standards can trigger the growth of microorganisms that affect patient conditions. This study aims to design and build an Internet of Things (IoT)-based system for detecting alcohol, cigarette smoke, temperature, and humidity levels to support real-time monitoring of hospital environmental quality. This system uses an MQ-3 sensor to detect alcohol levels, an MQ-135 to detect cigarette smoke, and a DHT22 to maintain air temperature and humidity. The measurement data is processed using an ESP8266 microcontroller and sent to an IoT platform so that it can be monitored directly through digital devices. The results of the design show that the IoT system is capable of continuous, accurate, and efficient environmental monitoring and provides early warnings.